2022
DOI: 10.1155/2022/5731372
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Inhibits Mesaconitine-Activated TRPV1-Channel-Induced Cardiotoxicity

Abstract: Aconiti Kusnezoffii Radix (Caowu) is often combined or processed with Chebulae Fructus (Hezi) to achieve attenuation purposes in Mongolian medicine. Mesaconitine (MA), a main bioactive ingredient of Caowu, is also famous for its high cardiotoxicity while exerting good anti-inflammatory and analgesic properties. Gallic acid (GA), one of the leading chemical components in Hezi, possesses cardiac protection. This study aimed to clarify the detoxification effects of GA from Hezi on MA-induced cardiotoxicity and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We also demonstrated that chebulagic acid in CF has a protective effect on myocardial mitochondria, and can inhibit aconitine-induced Ca 2+ overload in myocardial cells, thereby reducing the occurrence of arrhythmia ( Han et al, 2020 ). In addition, we also found that the TRPV1 channel have an important role in exerting their attenuated effects, the gallic acid in CF may achieve the effect of detoxification by rapid desensitization of TRPV1 channel on the cells ( Han et al, 2022b ; Mi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We also demonstrated that chebulagic acid in CF has a protective effect on myocardial mitochondria, and can inhibit aconitine-induced Ca 2+ overload in myocardial cells, thereby reducing the occurrence of arrhythmia ( Han et al, 2020 ). In addition, we also found that the TRPV1 channel have an important role in exerting their attenuated effects, the gallic acid in CF may achieve the effect of detoxification by rapid desensitization of TRPV1 channel on the cells ( Han et al, 2022b ; Mi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 80%
“…They reduce cardiotoxicity by involving numerous protein functions, signaling pathways, and biological processes ( Li et al, 2018 ). Our research group has verified that tannins and phenolic acids from CF can significantly reduce the mitochondrial membrane potential elevation and intracellular Ca 2+ overload caused by aconitine and MA in rat H9c2 cardiomyocytes through the TRPV1 channel, thereby improving mitochondrial function and inhibiting the cardiotoxicity of aconitine ( Han et al, 2020 ; Han et al, 2022b ; Han et al, 2022c ). When we were committed to the study of tannins, we accidentally found that triterpenoids in CF, while not as abundant as tannins, have a significant impact on antioxidant and cardioprotective properties.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In clinical applications, the combination of drugs can enhance the effect and mitigate aconite toxicity. Gallic acid can mitigate the toxicity of neoaconitine by inhibiting intracellular Ca 2+ influx, restoring mitochondrial membrane potential, and reducing apoptosis ( Han S. et al, 2022 ). In addition, berberine was found to prevent aconite-induced acute myocardial injury and arrhythmia, which may be related to the inhibition of aconitine-induced delayed depolarization and triggering activity ( Chen et al, 2018 ).…”
Section: The Toxicity-effect Profile Of Toxic Tcmmentioning
confidence: 99%